El documental histórico en los primeros años de la transición. Permiso para pensar (E. Meilij, 1989), un caso atípico - Marta Noemí Rosa Casale (Nuevo mundo - Mundos Nuevos, 2013)
The production of documentary films on politics was significant during the Alfonsín Government. At that time films that dealt with past political events cast a view of ample scope in order to cover deeds quite distant in time with the aim of reaching a conciliatory discourse vis á vis party lines. Their impact allows for the conclusion of a relatively important influence on the electorate at the time of the ballot. In this respect, Permission to think, the first and only film work of Eduardo Meilij, law practitioner, is an exception both with regard to its style and ideological conception: it radically departs from most of the production at that time. The film focuses on the years of the First Peronist government concentrating on the figures and characters of both Juan Domingo and Eva Perón from a pressumed “objective” point of view based on official propaganda documents of the times. Nevertheless, from the start it is clear that the film projects a critical and absolutely negative view about its central characters. This paper aims at discussing and answering this seeming paradox in detail.